The Association Between Spiritual Intelligence and Awe in University Students of Pakistan (Journal of Social Sciences Review, 2025)
Spiritual intelligence, a core component of spirituality, is conceptually related to awe, especially in the domain of transcendence. Awe is a self-transcendent emotion that involves the perception of vastness and a subsequent need for accommodation. Awe has been found to have several benefits for the individual self as well as social groups, making its experience of particular interest. This research investigated the association between spiritual intelligence and situational awe in 200 Pakistani university students between the ages of 18 and 25. A correlational, cross-sectional survey was carried out using The Spiritual Intelligence Self-Report Inventory (SISRI 24) and the Situational Awe Scale to test whether the variables were correlated and if age and gender influenced the experience of awe. The results revealed a significant positive association between spiritual intelligence and the experience of awe, indicating that individuals with higher levels of spiritual intelligence tended to experience awe to a greater extent. Additionally, a gender difference was observed, with women reporting higher levels of awe compared to men. No support was found for an age-based variation in situational awe. These findings contribute to the existing body of literature on spiritual intelligence, spirituality, and awe, particularly within the context of Pakistan, and have broad implications for various subfields within psychology.
Keywords: Awe; Spirituality; Spiritual Intelligence; Gender; Age